Rich Dad, Smart Dad: Decomposing the Intergenerational Transmission of Income - Lefgren, Lars; Lindquist, Matthew J.; Sims, David (Journal of Political Economy, 2012)
We construct a simple model, consistent with Becker and Tomes, that decomposes the intergenerational income elasticity into the causal effect of financial resources, the mechanistic transmission of human capital, and the role that human capital plays in the determination of fathers’ permanent incomes. We show how a particular set of instrumental variables could separately identify the money and human capital transmission effects. Using data from a 35 percent sample of Swedish sons and their fathers, we show that only a minority of the intergenerational income elasticity can be plausibly attributed to the causal effect of fathers’ financial resources.